Five day course in thinking - "Bono, Edward De" (England, 1967)
In this book he offers a series of simple but intriguing problems in thinking that require no special knowledge and no mathematics the problems are designed to let readers find out about their personal style of thinking, its weaknesses and strengths, and the potential methods that they never use being right is not always important- an error can lead to the right decision.
Keywords: Thinking course